ANALISIS IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK PENYANDANG DISABILITAS YANG ADA DI INDONESIA - Aida Ardini; Dinda Sukma Melati (Jurnal Hukum Lex Generalis, 2025)
People with disabilities or the term often heard as people with disabilities is as in accordance with the main points in the contents of the Convention on The Rights of Persons with Disabilities (CPRD) which has been ratified in Law Number 19 of 2019 where the term for those who have limitations, whether physical, mental, sensory or intellectual, with a long period of time in carrying out their daily lives, find obstacles in participating and efficient fulfillment of rights in equality. Therefore, the role of awareness of the surrounding community, such as parents, relatives or neighbors around the environment, is very much needed as figures who support, protect, and help people with disabilities in carrying out their daily lives. In addition, the role of the government is also equally important in providing protection for people with disabilities as a whole